2017
DOI: 10.1111/gfs.12334
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of perennial ryegrass‐ and tall fescue‐based swards with or without a cropping component for dairy production: Animal production, herbage characteristics and financial performance from a 3‐year farmlet trial

Abstract: Perennial ryegrass/white clover swards have some limitations in temperate grazed dairying systems. This study tested the hypothesis that farmlets based on alternative species would be equally or more profitable than those perennial ryegrass‐based, and would produce more herbage in summer‐dry conditions. Six farmlets were established; three with perennial ryegrass‐ and three with tall fescue‐based swards. For each grass species, one farmlet was solely based on grass‐clover swards while the other two had either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
3
4
0
Order By: Relevance
“…Protein contents did not differ significantly between LoPe and FeAr which confirms the findings of and of Lee et al (2018) We found that the protein contents developed differently in time for LoPe and FeAr mixtures: in late summer and autumn the protein contents of LoPe were higher than those of FeAr (Figure 1).…”
Section: Persistence Of Main Species and Feed Qualitysupporting
confidence: 87%
See 2 more Smart Citations
“…Protein contents did not differ significantly between LoPe and FeAr which confirms the findings of and of Lee et al (2018) We found that the protein contents developed differently in time for LoPe and FeAr mixtures: in late summer and autumn the protein contents of LoPe were higher than those of FeAr (Figure 1).…”
Section: Persistence Of Main Species and Feed Qualitysupporting
confidence: 87%
“…However, the net energy content in LoPe mixtures, although containing PoPr and HoLa which have a lower content of net energy , was higher than that of FeAr and PhPr mixtures. In this respect the results of the presented experiment are comparable to those with single-species swards with LoPe, FeAr and PhPr Davies and Morgan, 1982;Lee et al, 2018).…”
Section: Persistence Of Main Species and Feed Qualitysupporting
confidence: 74%
See 1 more Smart Citation
“…Davies and Morgan (1982) compared FeAr, LoPe and PhPr and found the highest in-vitro digestibility of 70% for LoPe (11.2 MJ ME/kg DM) but only 62% in-vitro digestibility and 9.9 MJ ME/kg DM for FeAr. Lee et al (2018) in a three-year field trial found that LoPe had a significantly higher content of metabolizable energy (ME) (12.1 MJ/kg DM) than FeAr (11.8 MJ/kg DM). Kalzendorf and Hinrichsen (2017) found for pure swards of LoPe in the first, second and third cut a content of net energy of always more than 6.3 MJ/kg DM while the net energy content of FeAr at each cut was below 6.0 MJ/kg DM.…”
Section: Effects Of Competition Of Species On Net Energy Content and ...mentioning
confidence: 99%
“…Most pastures utilized for dairy production in temperate environments are primarily composed of perennial ryegrass and white clover (Lee et al, 2018). These pastures provide highquality forage predominantly during the cool season but are characterized by low taxonomic and phytochemical diversity, presenting limited benefits to the cows and the environment (Distel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%